DIAGNOSTIC SIGNIFICANCE OF HEMATOLOGICAL TESTS IN CLINICAL LABORATORIES - G’aniyeva Sitora,; Nurmatova M.A., (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article discusses the diagnostic significance of hematological tests in clinical laboratories. The structure of blood and its main components, the clinical value of the complete blood count, and its role in the diagnosis of various diseases are analyzed. In addition, the importance of modern hematology analyzers in the diagnostic process is highlighted.